Effect of erythorbic acid administration on activities of drug metabolic enzyme and phosphatases in guinea pigs administered an adequate amount of ascorbic acid - Suzuki, E. (Ochanomizu Univ., Tokyo (Japan). Inst. of Environmental Science for Human Life); Kurata, T; Arakawa, N (Journal of Nutritional Science and Vitaminology, 1989)
The effect of erythorbic acid (ErA) administration on activities of liver aniline hydroxylase, liver acid phosphatase, and serum alkaline phosphatase, and the content of liver cytochrome P-450 was studied to determine whether or not ErA would affect the availability of ascorbic acid (AsA) in normal and AsA-deficient guinea pigs. In experi-ment I, changes of the enzyme activities and liver cytochrome P-450 content in the guinea pigs administered AsA and/or ErA and sacrificed on days 4, 10, 16, and 30 were examined. Moreover, in experiment II, after 16 days of depletion of AsA, the guinea pigs were administered AsA and/or ErA. These animals were sacrificed on days 0, 4, and 20 of the repletion period, after which the activities of drug metabolic enzyme and phos-phatases and content of cytochrome P-450 during recovery were observed. The enzyme activities and cytochrome P-450 content of AsA-supplemented guinea pigs were similar to those of ErA-supplemented animals and also similar to those of both AsA and ErA-supplemented guinea pigs throughout the experimental period. During the repletion of the AsA-depleted guinea pigs, there were no significant differences in these enzyme activities and cytochrome P-450 content among the animals administered AsA and/or ErA. These results suggested that ErA adminis-tration may not affect the AsA availability in the guinea pigs.